New Plant Records and Critical Notes on some Plants from South Bihar - Kanodia, K. C.; Malick, K. C. (Indian Forester, 1966)
Begonia concanensis A.DC., Anotis foetida Benth. Et Hook. F., Physalis longifolia Nutt., Vanda caerulea Griff. Ex Lindl., Ischaemum timorense Kunth and Setaria pallide-fusca Stapf et Hubb. Have been collected from Chhotanagpur area (Ranchi and Hazaribag Districts) in South Bihar and reported for the first time from Bihar State. Additional critical notes on some of these and in particular on Pennisetum hordeoides Steud., and Chrysopogon serrulatus Trin. Have also been presented in this paper.